Recovery of wasted fruit and vegetables for improving sustainable diets. (January 2020) - Augustin, M.A.; Sanguansri, L.; Fox, E.M.; Cobiac, L.; Cole, M.B.
Abstract: Background: Fruits and vegetables are an excellent source of nutrients, with numerous health benefits. Most consumers are not meeting the daily recommended intake of fruits and vegetables. Yet, a significant amount of fruits and vegetables that is produced is wasted. There are opportunities to recover the wasted fruits and vegetables for manufacturing value-added products to improve the sustainability of healthy diets and reduce the environmental footprint. Scope and approach: We discuss the challenges and opportunities in collection of food loss in the horticultural chain for return to the human food supply, science-based strategies that underpin the recovery and conversion of food loss from farm to retail into value-added safe and nutritious food ingredients and products, and use of food processing and stabilising technologies to recover fruits and vegetables for producing safe, healthy and nutritious foods. We advocate for a whole of value chain approach for capturing market-led business opportunities in the agri-food system to reduce food wastage and increase the availability of fruit and vegetable-based foods for consumers. Key findings and conclusions: The conversion of edible biomass that is currently lost to the food supply into safe, nutritious and appealing products could help contribute to the mitigation of low nutrient intakes of at-risk nutrients for vulnerable populations by driving higher consumption of fruits and vegetables. The recovery of wasted horticultural produce for return to the food supply improves the sustainability of the food system. It requires the establishment of a new value chain for the sector. Highlights: Edible horticulture loss is a new source of raw ingredients for the food industry. Converting horticulture loss into nutritious foods improves sustainability of diets. Processing enables production of value-added food products from edible waste. A transdisciplinary approach facilitates capture of markets for horticultural loss.